Development of the Early Axon Scaffold in the Rostral Brain of the Small Spotted Cat Shark (Scyliorhinus canicula) Embryo. (28th October 2014) - Ware, Michelle; Waring, Colin P.; Schubert, Frank R.
Abstract : The cat shark is increasingly used as a model for Chondrichthyes, an evolutionarily important sister group of the bony vertebrates that include teleosts and tetrapods. In the bony vertebrates, the first axon tracts form a highly conserved early axon scaffold. The corresponding structure has not been well characterised in cat shark and will prove a useful model for comparative studies. Using pan-neural markers, the early axon scaffold of the cat shark, Scyliorhinus canicula, was analysed. Like in other vertebrates, the medial longitudinal fascicle was the first axon tract to form from a small cluster of neurones in the ventral brain. Subsequently, additional neuronal clusters and axon tracts emerged which formed an array of longitudinal, transversal, and commissural axons tracts in the Scyliorhinus canicula embryonic brain. The first structures to appear after the medial longitudinal fascicle were the tract of the postoptic commissure, the dorsoventral diencephalic tract, and the descending tract of the mesencephalic nucleus of the trigeminal nerve. These results confirm that the early axon scaffold in the embryonic brain is highly conserved through vertebrate evolution.